Hubungan Pengetahuan Gizi Ibu dan Pola Asupan Makan Balita terhadap Status Gizi Balita di Kelurahan Kelapa Dua Wetan-Jakarta Timur - Febriyanti Zulyani; Diana Dwi Hartati; Bhakti Gunawan (Pusat Riset dan Inovasi Nasional, 2025)
Mother's knowledge of nutrition is one of the indirect factors that contribute to nutritional problems in toddlers. Toddler food intake is one of the direct factors that cause nutritional issues. Toddler food intake should be accompanied by balanced nutrition. The aim of this study is to examine mothers’ knowledge about balanced nutrition, toddler food intake, and toddler nutritional status at the Posyandu in Kelapa Dua Wetan Subdistrict, East Jakarta, as well as to analyze the relationship between toddler food intake and their nutritional status at the same location. The research method used was a descriptive observational study with a cross-sectional approach, involving a total sample of 114 mother–toddler respondents. The data processing techniques in this study included four stages: editing, coding, transferring, and tabulating. Meanwhile, the data analysis consisted of descriptive analysis to describe mothers’ knowledge of balanced nutrition and toddler food intake. Further analysis used bivariate analysis to determine the relationship between variables by applying the Chi-Square test. The results showed that 15.8% of toddlers had an overnutrition status, 60.5% had good nutritional status, and 23.7% were undernourished. After analyzing the data using the Chi-Square test, the p-value was found to be 0.0001 < 0.05, indicating a significant relationship between mothers’ knowledge of balanced nutrition and toddler food intake with toddler nutritional status at the Posyandu in Kelapa Dua Wetan Subdistrict, East Jakarta.